Pengaruh Kepemimpinan Transformasional, Motivasi Kerja dan Budaya Organisasi terhadap Kepuasan Kerja serta Dampaknya pada Kinerja Pegawai - Chandra Lukita (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2017)
The objective of this this research is to investigate, analyze, and interpret Transformational Leadership,Work Motivation, and Organizational culture toward Employee satisfaction in English Courses in the regionCiayumajakuning, and also the effect of employee satisfaction on Employee performance in English courses inCiayumajakuning region. The method used in this research is explanatory survey method, a method that is used to connectvariables and test these variables which are examined. Sample used is on 357 employees. The data wasanalysed by SEM (structural equation modeling) to explain the relationships and influence between themanifest variables and confirmatory analysis. In general, the research concludes that: 1) there is positive and significant influence that can becharacterized as partial or simultaneous: the influence of Transformational Leadership, Work motivation andorganizational culture on employee satisfaction. 2) there is positive and significant effect of employeesatisfaction on employee performance in English courses in the Ciayumajakuning region.